"COVID-19 is an Opportunity to Rediscover Ourselves": Reflections of a Novice EFL Teacher in Central America. (April 2023) - Farrell, Thomas S C; Stanclik, Connie
This article presents a case study that examined the principles and practices of one novice English as a foreign language (EFL) teacher at a prominent English language institution in Central America. This qualitative study sought to contribute to the discussion of the perceived interdependent influences of EFL teachers' thoughts, identities, and behaviors through five stages of self-reflection in Farrell's framework for reflective practice. The EFL teacher engaged in conscious reflection to subject their beliefs to critical analysis and interpretation expressed through their philosophy, principles, theory, practice, and beyond practice. Overall, the findings confirm that reflections in all five stages are connected to several common themes, but simultaneously reveal a complex relationship between the teacher's stated principles and actual practice. The discussion explores potential reasons for convergence and divergence in teachers' beliefs and classroom actions, concluding that the results correlate with previous research in the field of language education and teacher reflection.